Postdevelopmental model of cooperation for social intervention with minors in risk contexts in Tetouan-Morocco - Gutiérrez Sánchez, José David; Diz Casal, Javier (Revista Española de Desarrollo y Cooperación, 2023)
The traditional model of cooperation to the development carried out in the north of Morocco in last decades needs an evolution of techniques and means used to develop social interventions with children in risk contexts that notably promote their social and labor (work) integration. The article tries to emphasize how those interventions, carried out before to the economic and financial crisis, haven´t been able to empower the non-governmental organizations orientated to protect and improve the situation of childhood, which have undermined the entrepreneurial capacity of individuals, their social participation and transformative power of social context. Therefore, a model that expands its management capacity and facilitates individual and collective development relevant to today’s society is identified, making active and prepared individuals for the social change that is presented as a challenge towards the improvement of the potentials in childhood.